FIGURE 4 in Crangonyx islandicus sp. nov., a subterranean freshwater amphipod (Crustacea, Amphipoda, Crangonyctidae) from springs in lava fields in Iceland - N, Jörundur Svava R S S O; Kristjánsson, Bjarni K. (Zenodo, 2006)
FIGURE 4. Crangonyx islandicus sp. nov., female paratype, 6.2 mm, Vatnsvik. A, pereopod 3. B, Published as part of N, Jörundur Svava R S S O & Kristjánsson, Bjarni K., 2006, Crangonyx islandicus sp. nov., a subterranean freshwater amphipod (Crustacea, Amphipoda, Crangonyctidae) from springs in lava fields in Iceland, pp. 1-17 in Zootaxa 1365 on page 9, DOI: 10.5281/zenodo.174801